Home network in direct current powered by photovoltaic energy - Pereira, Renato Tadeu; Monteiro, Luiz Jerônimo Melo; Reis, Mari Aurora Favero; Ferreira, Fernanda Cristina Silva (Latin American Journal of Energy Research, 2024)
There is a growing demand for energy production methods that are more efficient and less polluting. Considering this prevalent view in the market, the most rapidly growing choice in recent years has been photovoltaic solar energy. It is crucial to emphasize studies to improve this technology as a clean and sustainable energy source. The project aims to design a domestic direct current (DC) network, using an Off-Grid photovoltaic system as the generating unit. Among the advantages are: reduction of energy losses in the form of heat during the conversion process to alternating current (AC); elimination of people’s exposure to dangerous voltages, thereby avoiding potential accidents; functioning as a backup power system for appliances. The implementation of the system includes lighting circuits and a video monitoring system powered at 12 volts, as well as USB (Universal Serial Bus) sockets operating at 5 volts, both of which are supplied with direct current. The components for generation, distribution, and consumption were dimensioned, and a part of the project was tested in a proportionally assembled prototype. Based on the studies and tests, the system proved feasible according to the initial objectives, although it presented some drawbacks compared to the conventional power grid. Nevertheless, it can be considered viable for implementation due to its positive cost-benefit ratio.